The challenges of transgender and nonbinary graduate students in chemistry: A qualitative study on trans identity, science culture, and institutional support using reflexive thematic analysis - Michelle M. Nolan; Isaac M. Blythe; Paulette Vincent-Ruz (PLoS ONE, 2025)
Transgender, nonbinary, two spirit, and gender-expansive students (herein trans students ) are marginalized in higher education and have significantly different college experiences than their cisgender peers. Using in-depth interviews modeled after Sista Circles methodology and applying reflexive thematic analysis, this qualitative research illuminates the nuanced experiences of trans students navigating chemistry PhD programs ( N = 10). The participants’ counterstories revealed tensions between their identities as trans people and their identities as chemists, where STEM professional culture encouraged the participants to cover and separate their transness from their graduate education. The data demonstrated that these students navigated a complicated process when choosing a graduate program and deciding whether to share their trans identities in their institutions. Participants also encountered cisnormative institutional structures, including program applications and information technology systems, which enforced usage of their legal name and gender marker data in the academy. These results highlight disparities between institutional rhetoric regarding LGBTQ+ inclusion and tangible support for trans graduate students. From grappling with the absence of supportive policies to advocating for institutional change, participants confronted systemic barriers that impeded their academic and personal growth. This study underscores the imperative for transparent and proactive support structures within STEM academic departments to foster an environment where trans individuals can thrive.